ANALYSIS OF STATE PROPERTY ADMINISTRATION THROUGH STATE PROPERTY MANAGEMENT AND ACCOUNTING INFORMATION SYSTEM (SIMAK-BMN) AT THE PALU RELIGIOUS HIGH COURT REGIONAL COORDINATOR - Sarif, Sarman; Ridwan, Ridwan; Kasim, Muhammad Yunus (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aims to describe the process of administering State Property at the Regional Coordinator of the Palu Religious High Court and to offer solutions in the perspective of basic accounting concepts. This research used a qualitative method with a post-positivism approach. The data collection process was carried out through observation, interviews, and documentation analysis using the triangulation model technique. The research results show that (1) that registration is application-based but there are still items that have not been coded according to the type of goods, recording is not supported by valid source documents and updating of data and information on State Property is not carried out regularly, (2) recording is not supported by documents valid sources, (3) State asset data and information are not updated regularly, (4) Inadequate inventory of State Property, (5) State Property reports have not been reported in a timely manner. An alternative to the concept of State Property Administration in the prospect of basic accounting concepts is entity theory, such as: (1) In bookkeeping, it is necessary to have an understanding of the recording of State property, both goods purchased through the State Budget, Grants and Inbound Transfers so that the difference in the presentation of State Property books is not occurs., (2) In the inventory it is necessary to update State property that is no longer in accordance with the needs or obsolete goods, (3) In reporting the need for detailed presentation of goods so that it is easy to present in the state property report (4) In the use of a system application in asset management, it is very necessary to have real policies related to the use of applications according to needs, so that the asset administration process can run effectively and efficiently, (5) Asset reports will be complete and reliable if there is a match between physical assets, ownership documents and records in the books inventory. Mechanism of State Property Administration g is good, then the process of transparency and accountability in the management of State Property will be realized. Keywords : Administration, State Property, SIMAK-BMN Application